Development and sensorial acceptance of biofortified dehydrated cassava chips - Oliveira, Luciana Alves de; Reis, Ronielli Cardoso; Santana, Hannah Miranda; Santos, Vanderlei da Silva; Viana de Carvalho, José Luiz (Universidade Estadual de Londrina, 2017)
Cassava is the food base for millions of people in tropical Africa, Latin America and Asia. However, cassava commercial varieties are deficient in vitamin A and the consumption of biofortified cassava, which has a higher concentration of Beta-carotene in the roots, represents an alternative to prevent this deficiency. Dehydrated products are an integral part of many consumers’ diet, which have preferred healthier and lower calorie foods. This study aimed to develop a dehydrated product of cassava (dehydrated chips) from biofortified varieties. The dehydrated chips were elaborated from the following biofortified cassava genotypes: BRS Dourada, BRS Gema de Ovo, BRS Jari and hybrid 2003 14-11. For obtaining the dehydrated chips, cassava roots were washed, sanitized, peeled, sliced to a thickness of 0.8 mm, blanched and dehydrated at 65 °C. First, dehydrated chips were prepared with no added flavoring, from roots of four cassava genotypes harvested at 12 months after planting, in order to select the two most suitable for dehydrated chips production based on sensory acceptance. In the second stage, dehydrated chips were produced with the addition of onion and parsley flavoring, from the two genotypes selected in the previous step. The BRS Jari variety and hybrid 2003 14-11 showed highest total carotenoid content, 10.54 ?g g g-1 and 6.92 ?g g g-1, respectively, and Beta-carotene, 8.93 ?g g g-1 and 4.98 ?g g g-1, respectively. For carotenoids and Beta-carotene retention there was no significant difference among the dehydrated chips prepared with four biofortified cassava genotypes, which showed average values of 76% and 67%, respectively. Dehydrated chips made with the BRS Jari and hybrid 2003 14-11 had highest average for flavor attribute and did not differ on the crispness and overall acceptance and classified between "like slightly” and "like moderately”. Despite the addition of "onion and parsley" flavoring, there has been no greater acceptance by consumers. Dehydrated cassava chips made with the BRS Jari variety and the hybrid 2003 14-11 showed good sensorial acceptance and higher total carotenoid and Beta-carotene contents, thus being biofortified varieties suitable for the elaboration of this product.